Women's Perceptions of Medication Use During Pregnancy and Breastfeeding: A Swedish Cross-sectional Questionnaire Study. Issue 2 (June 2020) - Wolgast, E.; Lindh-Åstrand, L.; Lilliecreutz, C.
Abstract : ( Acta Obstet Gynecol Scand . 2019;98:856–864) Medications are used frequently during pregnancy to treat an array of symptoms and conditions, from diabetes and asthma to nausea and depression. Women may view medication use as potentially unsafe during pregnancy, particularly due to the thalidomide scandal of the 1960s. One study on herbal medicine use during pregnancy found that 19% of women used herbal medicines during pregnancy and 20% believed they were safer than prescribed medications. This current study examined the perceptions among Swedish pregnant women of overall medication use and herbal medicine use during pregnancy and postpartum when breastfeeding. They also investigated patients' sense of reliability of the sources from which they got their information about medication use during pregnancy.